The Development of An Analytical Overlay Design Procedure - Djunaedi Kosasih (Civil Engineering Dimension, 2008)
Pavement structural evaluation using pavement modulus values resulting from back calculation process on non-destructive deflection data has been adopted to quantify objectively the conditions of existing pavements under various traffic loading and environmental conditions. However, such an advanced technique is not yet followed widely by advances in analytical overlay design procedures. One possible reason is perhaps due to its requirement to perform complex computations. A new module of computer program BackCalc has been developed to do that task based on the allowable maximum deflection criterion specified by the Asphalt Instituteâ83. The rationale is that adequate overlay thickness will be computed by iteration to result in theoretical maximum deflection that closely matches against the specified allowable maximum deflection. This paper outlines the major components of the program module illustrated by using a practical example. The overlay thickness obtained was found to be comparable with that of the known AASHTOâ93 method